2010
DOI: 10.2106/jbjs.h.01527
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Clinical Findings and Magnetic Resonance Imaging for the Diagnosis of Chondromalacia Patellae

Abstract: Chondromalacia patellae cannot be diagnosed on the basis of symptoms or with current physical examination methods. The present study demonstrated no correlation between the severity of chondromalacia patellae and the clinical symptoms of anterior knee pain syndrome. Thus, symptoms of anterior knee pain syndrome should not be used as an indication for knee arthroscopy. The sensitivity of 1.0-T magnetic resonance imaging was low for grade-I lesions but considerably higher for more severe (grade-II, III, or IV) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 23 publications
1
60
0
4
Order By: Relevance
“…The available measurements are inadequate in reflecting the actual patellar alignment, and studies have contradicting results regarding normal measurements of the congruence angles [20,21]. Arthroscopy is a reliable diagnostic method; however, surgical treatment for CMP is indicated in less than 10% of patients [22]. MRI is the imaging modality that should be chosen for non-interventional diagnosis of CMP [21].…”
Section: Discussionmentioning
confidence: 99%
“…The available measurements are inadequate in reflecting the actual patellar alignment, and studies have contradicting results regarding normal measurements of the congruence angles [20,21]. Arthroscopy is a reliable diagnostic method; however, surgical treatment for CMP is indicated in less than 10% of patients [22]. MRI is the imaging modality that should be chosen for non-interventional diagnosis of CMP [21].…”
Section: Discussionmentioning
confidence: 99%
“…MRI is a valuable tool because it provides 3-dimensional views, does not use ionizing radiation, and evaluates the bone as well as the soft tissues. Pihlajamaki [24] found that MRI was an accurate diagnostic tool for severe cases of chondromalacia patella although the sensitivity for low grade lesions was lower. However, this study used 1.0 Tesla magnets rather than the more detailed MRIs available currently.…”
Section: Imagingmentioning
confidence: 99%
“…4,8,11 Most of the studies have taken clinical presentation of anterior knee pain as a reference standard for suspecting PFPS and some have used knee arthroscopy as a reference standard. [4][5][6][7]12,13 We proposed that just a mere presentation of the anterior knee pain without other identifiable causes cannot label a patient as having PFPS. Arthroscopy for a condition like PFPS which is treated mostly by physiotherapy is not routinely justifiable as it is an invasive procedure and has its own complications.…”
Section: Discussionmentioning
confidence: 99%